Multiple roles of the gene zinc finger homeodomain-2 in the development of the Drosophila wing. - Perea, D.; Molohon, K.; Edwards, K.; Díaz-Benjumea, F.J. (Mechanisms of Development, 2013)
The gene zfh2 and its human homolog Atbf1 encode huge molecules with several homeo- and zinc finger domains. It has been reported that they play important roles in neural differentiation and promotion of apoptosis in several tissues of both humans and flies. In the Drosophila wing imaginal disc, Zfh2 is expressed in a dynamic pattern and previous results suggest that it is involved is proximal-distal patterning. In this report we go further in the analysis of the function of this gene in wing development, performing ectopic expression experiments and studying its effects in genes involved in wing development. Our results suggest that Zfh2 plays an important role controlling the expression of several wing genes and in the specification of those cellular properties that define the differences in cell proliferation between proximal and distal domains of the wing disc.